Direitos das mulheres pela educação na perspectiva do silenciamento: funcionamento discursivo de Nísia Floresta e da ONU mulheres. - Cavalcanti, Erika Caroline de Oliveira (2022)
This research, which is characterized by qualitative and descriptive exploratory nature, aims to analyze from the perspective of silencing, the discursive operation of Nísia Floresta and UN Women on women's rights, through the role of Education. As an assumption, we consider that legal advances for the emancipation of women in society, although instituted, do not constitute effective cultural change that solidifies these rights, which implies silences about the topic in focus. To this end, and starting from the imbrication between language, history and subject, developed by the researcher Michel Pêcheux in the late 1960s and subsequent period, we propose, as theory and methodology, the Analysis of the French line speech (AD), from the unfolding of the author Eni Orlandi, which brings silence as an object of reflection. The theoretical discussion still covers, the issue of women's rights, as well as the listed discursive authors – Nísia Floresta and UN Women - and on the subject of Education. According to the present object of study, which consists of women's rights, we present, as a corpus for analysis, works by Nísia Floresta, recognized for being the author of the first records in the struggle for women's rights in Brazil and Latin America, and documents of UN Women, presented at the last World Conference on Women as a declaration and platform for action – and its consequences – for the contemporary world. For the analysis procedures, under the input of AD and its reflections on the analysis of silence, we seek the constitution of the speeches presented in front of production conditions in the construction of silences, in addition to producing meaningful effects, by understanding the interdiscourse in vogue, as well as the relationship between the ideological formations of the speech of Nísia Floresta and the speech of the UN Women from their positions-subject on women's rights through Education. In the final considerations, we consider that this discussion on rights, gender equality and equity are just the tip of the iceberg in front of the UN's 2030 agenda.